Pelagic Feeding Ecology of Dovekies, Alle alle, in Lancaster Sound and Western Baffin Bay - Bradstreet, Michael S.W. (ARCTIC, 1982)
Adult (AD), Subadult (SA), and hatching year (HY) dovekies were collected at sea in 1976, 1978, and 1979 (n=410) for food habits studies. In May and June, AD and SA dovekies ate mostly copepods (99.8% of dry weight in AD, 100% in SA); in August, amphipods became more important (59% in AD, 90% in SA). Adult males accompanied chicks to sea where both groups fed largely on Parathemisto amphipods (99.7% in AD, 97% in chicks). Once abandoned by the adults, HY dovekies ate Parathemisto (59.8% of dry weight), Apherusa glacialis (13.6%), and Onisimus glacialis (5.6%) amphipods; arctic cod (Boreogadus saida) (14.5%); calenoid copepods (5.5%); and other items (1%). Seasonal changes in diet were, in part, related to a presumed seasonal increase of suitable amphipods in surface waters. HY dovekie diets varied geographically and with year. Some food taxa were larger in dovekies collected in waters associated with an intrusive current flowing into and out of the mouth of Lancaster Sound than in those collected in offshore Baffin Bay. In 1978, Parathemisto and Apherusa glacialis were smaller than in 1979 or 1976: HY dovekies apparently compensated by taking more copepods. HY dovekies were smaller on a given date in 1978 but ate similar total amounts of food and grew at similar rates in all three years. The small size of amphipods in 1978 was probably due to unusually late breakup of ice and its probable inhibitory effects on primary and secondary production. In 1978, many non-breeding (AD and SA) dovekies molted in pack ice that persisted until mid-August. In 1979, when pack ice dispersed early, no non-breeding dovekies were collected in August.Key words: dovekie, Alle alle, trophic relationships, pelagic seabird ecology, arctic marine systems, molt